Work motivation of implementing nurses to improve the quality of health services - Rasi Rahagia; Fatimah Fatimah; Yoga Tri Wijayanti; Tunggul Sri Agus Setyaningsih; M. Khalid Fredy Saputra (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: The motivation of the implementing nurse is essential to improving the quality of health services. Implementing nurses plays a vital role in providing quality services to patients. High work motivation is crucial in enhancing nurses' performance and commitment to providing the best care.